2021
DOI: 10.1093/cvr/cvab367
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a high-fat diet on the metabolic profile and the phenotype of atrial myocardium in mice

Abstract: Aims Obesity, diabetes and metabolic syndromes are risk factors of atrial fibrillation (AF). We tested the hypothesis that metabolic disorders have a direct impact on the atria favoring the formation of the substrate of AF. Methods & Results Untargeted metabolomic and lipidomic analysis was used to investigate the consequences of a prolonged high fat diet (HFD) on mouse atria. Atrial properties were characterized by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Despite these established epidemiological observations, mechanistic approaches are severely lacking. Recently, a study published by Suffee et al using a high-fat-diet mouse model showed a vulnerability to AF linked to a shorter action potential duration caused by enhanced K-ATP current in the context of obesity ( 19 ). Although interesting, such studies did not emphasize the liver phenotype so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these established epidemiological observations, mechanistic approaches are severely lacking. Recently, a study published by Suffee et al using a high-fat-diet mouse model showed a vulnerability to AF linked to a shorter action potential duration caused by enhanced K-ATP current in the context of obesity ( 19 ). Although interesting, such studies did not emphasize the liver phenotype so far.…”
Section: Discussionmentioning
confidence: 99%
“…AF pathogenesis encompasses a wide spectrum of mechanisms involving electrophysiological and structural remodeling of the left atrium (LA) ( 15 ). Furthermore, metabolic disorders have been previously associated with LA remodeling [e.g., mitochondrial dysfunction in diabetic patients ( 16 18 ) and enhanced LA fibrosis in the high-fat-diet-fed mice ( 19 )] but did not emphasize the liver phenotype. Therefore, data assessing the impact of MAFLD on LA remodeling are severely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Both Pdk4 and HMGcs2 are differentially expressed in obese human hearts with hypertrophy ( Newman et al., 2017 ), which underscores the potential relevance of our findings to some forms of human heart disease. Another group has recently reported metabolomic changes in mouse atrial tissue in response to 16 weeks of HFD ( Suffee et al., 2021 ). Similar to our results from ventricular tissue, this study showed accumulation of some fatty acids and increased use of fatty acid as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized linoleic acid metabolites including 9-oxoODE were reduced 44 . Atrial fatty infiltration contributes to abbreviation of action potential duration and a substrate for AF, and oxidized lipid metabolites likely contribute to this process 45 .…”
Section: Discussionmentioning
confidence: 99%